Crustal structure of southern Madagascar from receiver functions and ambient noise correlation: Implications for crustal evolution. Issue 2 (3rd February 2017) - Rindraharisaona, E. J.; Tilmann, F.; Yuan, X.; Rümpker, G.; Giese, J.; Rambolamanana, G.; Barruol, G.
Abstract: The Precambrian rocks of Madagascar were formed and/or modified during continental collision known as the Pan‐African orogeny. Aborted Permo‐Triassic Karoo rifting and the subsequent separation from Africa and India resulted in the formation of sedimentary basins in the west and volcanic activity predominantly along the margins. Many geological studies have documented the imprint of these processes, but little was known about the deeper structure. We therefore deployed seismic stations along an SE‐NW trending profile spanning nearly all geological domains of southern Madagascar. Here we focus on the crustal structure, which we determined based on joint analysis of receiver functions and surface waves derived from ambient noise measurements. For the sedimentary basin we document a thinning of the underlying crystalline basement by up to ∼60% to 13 km. The crustal velocity structure demonstrates that the thinning was accomplished by removal or exhumation of the lower crust. Both the Proterozoic and Archean crust have a 10 km thick upper crust and 10–12 km thick midcrust. However, in contrast to the typical structure of Proterozoic and Archean aged crust, the Archean lower crust is thicker and faster than the Proterozoic one, indicating possible magmatic intrusions; an underplated layer of 2–8 km thickness is present only below the Archean crust. The Proterozoic mafic lower crust might have been lost during continental collision by delamination or subduction or thinned as a result of extensional collapse. Finally, the Cretaceous volcanics along the east coast are characterized by thin crust (30 km) and very large V P / V S ratios. Key Points: The crustal structure is strongly correlated with the different geological units The Archean crust is thicker than the Proterozoic and a mafic layer forms the bottom of the Archean crust but is absent in the Proterozoic The lower crust has been removed or thinned below the western Morondava basin